(untitled) (Medical Forum Monthly, 2024)
Objective: Despite being a serious hazard the causal factors and outcomes of burn injuries in Karachi remain an under researched area. The purpose of our study was to analyse the epidemiology and mortality of burn injury cases in Karachi in order to create awareness at mass level. Study Design: Prospective Observational Study. Place and Duration of Study: This study was carried out from October 30th, 2013 to April 30th, 2014 in the Burns Centre, Civil Hospital Karachi. Materials and Methods: The study encompassed all the burn injury cases (expired or alive) reported to the Civil Hospital during the six months of the study period. The demographic information, cause and level of injury of all the reported cases were documented. Results: 784 cases of thermal injuries were reported. Out of these, 441(56.25%) were males and 343(43.75%) were females. Most of the burn victims (60%) belonged to the age group of 15 – 44 years. Out of 784 cases, 565 cases (72%) were of serious dermo-epidermal and deep burns. The overall burn mortality rate was found to be 55.9%. This included burn victims who were brought dead or expired during treatment. Maximum burns were a result of fire/flame (48.1%). Conclusions: The mortality rate of burn injuries in Karachi is alarming as compared to the international statistics. Fire incidents are the main cause of these injuries. Fatal burns can be prevented if necessary precautions are taken.